AUTOIMMUNE HEPATITIS IN CHILDREN AND ADOLESCENTS: DIFFERENCES IN CLINICAL PRESENTATION, DIAGNOSIS AND MANAGEMENT - Katarzyna Łysynkiewicz; Zuzanna Wątek; Patrycja Krawczyk; Izabela Grzyb; Jan Szewczyk; Alicja Smolińska; Maria Bołoz; Sylwia Haba; Ewa Dapkiewicz; Dawid Gąsowski (Archiv Euromedica, 2026)
Background Autoimmune hepatitis is a chronic immune-mediated inflammatory liver disease with a heterogeneous spectrum, ranging from asymptomatic liver enzyme elevation to acute liver failure, cirrhosis, and liver transplantation. Juvenile autoimmune hepatitis is clinically important because it may present acutely and with advanced liver injury. Aims This narrative review summarizes current evidence on autoimmune hepatitis in children and adolescents, focusing on presentation, diagnosis, treatment, long-term care, and differences from adult management. Methods PubMed/MEDLINE and Google Scholar were searched for English-language publications from January 1997 to June 17, 2026. Forty-five publications were included in the narrative synthesis. Results Type 2 autoimmune hepatitis accounts for approximately one third of pediatric cases, and up to 80% of type 2 cases are diagnosed before age 18. Approximately 25-34% of pediatric patients may be asymptomatic, whereas 25-40% present acutely. Diagnosis requires biochemical, serological, histological, and differential assessment. Pediatric autoantibody thresholds may be lower than adult thresholds, including ANA/SMA ≥1:20 and anti-LKM1 ≥1:10. First-line therapy is corticosteroids with azathioprine; one pediatric study reported biochemical remission after a mean of 36 days. In 10–20% of cases, intolerance or inadequate response requires mycophenolate mofetil, tacrolimus, or cyclosporine. Conclusions Early recognition, individualized immunosuppression, and long-term follow-up are essential to achieve remission, prevent relapse, and reduce progression to end-stage liver disease.